Saint Leo's Church - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the exterior of Saint Leo's Church. The sign above the entrance arch reads "Mission by Paulist fathers. Saint Leo's Church. November 8 to 22, 1931. Invite your non-Catholic friends."